2023
DOI: 10.1038/s41598-023-38133-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparing machine learning algorithms to predict COVID‑19 mortality using a dataset including chest computed tomography severity score data

Abstract: Since the beginning of the COVID-19 pandemic, new and non-invasive digital technologies such as artificial intelligence (AI) had been introduced for mortality prediction of COVID-19 patients. The prognostic performances of the machine learning (ML)-based models for predicting clinical outcomes of COVID-19 patients had been mainly evaluated using demographics, risk factors, clinical manifestations, and laboratory results. There is a lack of information about the prognostic role of imaging manifestations in comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Shahriare Satu et al [26], the suggested technique may precisely predict the daily count of infected patients by training it using sample data from our web application's 25 days of data collection. Based on a larger dataset that includes the chest CT severity score (CT-SS), Seyed Zakariaee et al [27] proposed an efficient machine learning prognostic model. There were 55 primary features in 6 main classes based on retrospective reviews of 6854 probable cases.…”
Section: Related Workmentioning
confidence: 99%
“…Shahriare Satu et al [26], the suggested technique may precisely predict the daily count of infected patients by training it using sample data from our web application's 25 days of data collection. Based on a larger dataset that includes the chest CT severity score (CT-SS), Seyed Zakariaee et al [27] proposed an efficient machine learning prognostic model. There were 55 primary features in 6 main classes based on retrospective reviews of 6854 probable cases.…”
Section: Related Workmentioning
confidence: 99%
“…Investigating the variables correlated with the death of patients with COVID-19 in the ICU may be fundamental for understanding the disease and improving treatment strategies ( Liu et al, 2020 ; Pijls et al, 2021 ). Data of patients with COVID-19 has been explored utilizing ML to forecast their prognosis ( Kamel et al, 2023 ) because it represents a sophisticated and adaptable approach to classification modeling by analyzing large datasets to unveil significant latent relationships or patterns ( Zakariaee et al, 2023 ). Studies indicate that, in predicting clinical outcomes among COVID-19 patients, ML methods demonstrate superior accuracy compared to conventional statistical models ( Afrash et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have utilized different machine-learning algorithms to identify features that can be used to predict mortality in COVID-19 patients. These features include age [ 12 , 17 , 37 45 ], gender [ 11 , 18 , 28 , 37 , 39 , 40 , 43 46 ], dry cough [ 15 , 17 , 18 , 28 , 37 , 40 , 41 , 43 , 47 ], as the clinical symptom, underlying diseases including cardiovascular disease [ 37 , 38 , 40 42 , 46 , 48 , 49 ], hypertension [ 37 , 38 , 41 , 43 , 44 , 46 , 50 ], diabetes [ 37 40 ], neurological disease [ 37 , 39 , 40 ], cancer [ 12 , 37 , 40 , 43 , 49 ]. Additionally laboratory indices such as serum creatinine [ 37 , 40 ], RBC [ 37 ], WBC [ 15 , 37 , 43 ], hematocrit [ 37 ], absolute lymphocyte count [ 11 , 28 , 37 , 40 , 41 , 46 , 47 ], absolute neutrophil count [ 15 , 17 , 28 , 37 , 40 42 , 47 , ...…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies did not take into account important factors such as demographic, clinical, and laboratory predictors of COVID-19 mortality. It has been observed that these features have a correlation with the mortality of individuals during hospitalization [ 40 , 41 , 45 ]. To address this gap, new non-invasive digital technologies, including machine-learning prediction have been introduced for predicting the mortality of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%